Oncoplastic Approach to Giant Benign Breast Tumors Presenting as Unilateral Macromastia - Lekshmi Malathi (Indian Journal of Plastic Surgery)
Benign breast tumors attaining large size constitute an important cause of unilateral macromastia. Their usual treatment involves enucleation or excision with a margin based on pathology and waiting for spontaneous retraction of skin envelope. In very large tumors, this will leave the residual breast deflated and unaesthetic, with spontaneous skin retraction giving unpredictable results. Application of the principles of oncoplastic surgery are helpful in this situation. Here, we present two cases of benign giant tumors—a giant fibroadenoma and a giant lipoma—managed by reduction mammaplasty approach to restore the breast symmetry and aesthetics.